(untitled) (Revista de Ensino em Artes, Moda e Design, 2021)
Any object can become a biographical object from the construction of the facts, the time and the environment where it was inserted, in relation to human life. To understand the importance of the affective relationships between human beings and their biographical objects is the main objective for the development of this work. Including, it seeks to identify the relevance of affective relationships between people, by means of crocheting and its positive reflections for the collective memory. This bibliographical, qualitative research, which, in an expository way, recreates a theoretical context. By social design methodological approaches, it uses studies of articles and other scientific products. The affective relationships that are installed between human beings and these objects can also define the time, the place, the life history of an individual or social group, in short, situate the territory. Crochet handicraft can be executed in a group and, consequently, by group dedication, it becomes a tradition. It was observed that crochet can be applied to any object, as long as the creative potential and the research of materials are used. To meet the collective work, raw materials are sought in the region. It drives the movement of revaluing the “handmade”. In this way, it becomes possible to insert the affective relationships with the objects, the places, and the entire life history of an individual or social group.